Upaya promosi kesehatan gigi dan mulut pada lansia di indonesia - Hapsari Andayani, Lia (Fakultas Kedokteran Gigi Universitas Trisakti, 2023)
The proportion of elderly people in developed countries has increased significantly during the last decades. This demographic shift will have important implications for health care services. Oral health is a vital factor to improve the quality of life because it is related to the general health condition. This principle applies to all age groups including the elderly. The most common oral health problems encountered by the elderly are tooth loss, dental caries, periodontitis, xerostomia, oral lessions and dental problems. Poor oral health may lead to dehydration, malnutrition, and several other systemic diseases. With many degenerative diseases that they may experience, it is difficult for them to access the basic practice of oral health management such as tooth brushing or denture hygiene. Therefore, it is considered necessary to provide professional approach to help increase awareness of elderly in maintaining their oral health. National health authorities should develop policies and measurable goals regarding oral health for elderly. National public health programmes should consist oral health promotion and disease prevention based on identified risk factors as well as using the right approach.